New windows on the universe : advances in multimessenger astronomy - Vrtilek, Saeqa Dil (IOP (Series). Release 22., 2022)
This book provides examples of multi-wavelength and multimessenger studies within astronomical research. The examples range widely over topics at the forefront of contemporary research and include colliding black holes and neutron stars, the discovery of planetary systems around stars other than our own, and the determination of the Hubble constant which sets the size and age scales of our universe.